Truncated Thioredoxin Peptides Serves as an Efficient Fusion Tag for Production of Proinsulin - Nataraj, Nandini B.; Sukumaran, Sunil K.; Sambasivam, Ganesh; Sudhakaran, Raja (Protein and Peptide Letters, 2020)
Background: Insulin is a peptide hormone used for regulating blood glucose levels. Human insulin market is projected to grow at a rate of 12.5% annually. To meet the needs of patients, a cost effective insulin manufacturing strategy has to be developed. This can be achieved by selecting a competent host, ideal fusion tag and streamlined downstream process. Objective: In this article, we have demonstrated that selecting a right fusion partner for expression of toxic proteins like insulin, plays a major role in increasing the recombinant protein yield. Methods: In this article, we have focused on identifying a peptide tag fusion partner for expressing proinsulin by truncating thioredoxin tag. Truncations were carried out from both Amino and Carboxy terminus of the protein and efficiency of truncated sequences was evaluated by expressing it with proinsulin gene. FCTRX (1-15) sequence fused to proinsulin was processed further to establish downstream protocol for purification. Results: Thioredoxin tag was truncated appropriately by considering the fusion tag: protein ratio. A couple of sequences ranging 10 – 15 amino acids were identified based on its in silico properties. Of these FCTRX (1-15) showed increased expression and stability of fusion protein. 156 mg of purified insulin was generated from 1g of inclusion body after enzymatic conversion and chromatographic steps. Conclusion: As a result of the current study, it was concluded that FCTRX (1-15) peptide has advantageous attributes to be considered as an ideal fusion tag for expression of proinsulin. This can be further explored by expressing it with other proteins.
Keywords: proinsulin